The Role of Relationships in Resilience: Teachers Who Were At-Risk Youth Supporting At-Risk Students - Laura I. Sigad (MDPI AG, 2023)
Despite extensive research on resilience, little information exists on the resilience of teachers who faced adversity in childhood and the meanings they attribute to their current work with at-risk students. Thus, this study aimed to address this knowledge gap by examining the narratives of teachers who were at-risk children. Based on 30 semi-structured life-narrative interviews, the findings revealed the significant meaning that the participants ascribed to positive relationships. Whether such relationships were present or absent in their childhood, these relationships were instrumental in their choice to pursue a career in education. In supporting their students' resilience and becoming the teachers they wanted as children, they found meaning in their past experiences of risk and coping. The study's discussion applies the social mirroring theory to analyze how the participants resisted the negative image presented to them by others in their childhood and how a belief of hopeful prospects fortified them and led them to take on transformative justice as their life mission. Supporting at-risk children functioned as a form of healing for the participants, fostering both their students' and their own resilience. The study findings highlight the importance of accounting for teachers' childhood experiences as formative narratives that mold their educational work.